Selling Eden: Environmentalism, Local Meat, and the Postcommodity Fetish. (July 2019) - Stanescu, Vasile
Advocates for eating locally raised animals claim that their practice is helpful in protecting the environment. However, the opposite is true. As such, their references to "nature" have less to do with a scientific stable ecosystem and, instead, represent a call for a return to a "natural" order of human's supposedly benevolent domain over other animals. Instead of a science-based environmental policy, local meat operates as a type of "postcommodity fetish." It is because of the desire to escape the confines of consumerist culture, to return to romanticized idea of Edenic-purity, which underlies the desire to purchase "locally" produced animal products.